Experimental Analysis of Fuzzy Gain-Scheduled PID Controller With a Feedforward Compensator for an Ultra-Precise Piezoactuated Micropositioning Stage - Hussain Kahil; Irfan Ahmad; Yasser Bin Salamah (IEEE Access, 2025)
The piezoactuated micropositioning stage discussed in this study employs an all-ceramic insulation and a flexure-guide mechanism. It demonstrates remarkable capabilities, including achieving subnanometer resolution, high positioning accuracy, rapid response, and a high load capacity. The successful operation of this stage relies on the crucial role played by piezoelectric actuators. However, the inherent nonlinear hysteresis characteristics of these actuators, if not compensated for, can significantly compromise the precision of the positioning. This paper presents an experimental analysis of the piezoactuated micropositioning stage studied. Initially, a conventional proportional-integral-derivative (PID) feedback controller is utilized. Subsequently, intelligent fuzzy and fuzzy gain-scheduled PID feedback controllers are implemented, along with a hysteresis feedforward compensator. The main objective is to achieve ultra-precise positioning while avoiding the complexities associated with inverse hysteresis modeling. The experimental results from the piezoactuated micropositioning stage demonstrate the effectiveness of the intelligent fuzzy gain-scheduled PID controller with a feedforward compensator in achieving precise positioning. The peak-to-peak tracking error is 0.5% of the $12μ $ m, 10Hz reference trajectory, marking a 54% and 88% performance improvement over the intelligent fuzzy controller, and classical PID controller, respectively.